The discovery of VU0652957 (VU2957, Valiglurax): SAR and DMPK challenges en route to an mGlu4 PAM development candidate. Issue 2 (15th January 2019) - Panarese, Joseph D.; Engers, Darren W.; Wu, Yong-Jin; Guernon, Jason M.; Chun, Aspen; Gregro, Alison R.; Bender, Aaron M.; Capstick, Rory A.; Wieting, Joshua M.; Bronson, Joanne J.; Macor, John E.; Westphal, Ryan; et al.
Graphical abstract: Highlights: First description of the SAR that led to the discovery of VU2957 (Valiglurax). Valiglurax is only the second mGlu4 PAM clinical candidate for Parkinson's disease. The new series afford improvements in protein binding, half-life in vivo, CNS penetration and oral bioavailability. Highlights subtle differences in positioning of hydrogen-bond acceptors and impact on CNS penetration/P-gp liability. Abstract: This letter describes the first account of the chemical optimization (SAR and DMPK profiling) of a new series of mGlu4 positive allosteric modulators (PAMs), leading to the identification of VU0652957 (VU2957, Valiglurax), a compound profiled as a preclinical development candidate. Here, we detail the challenges faced in allosteric modulator programs (e.g., steep SAR, as well as subtle structural changes affecting overall physiochemical/DMPK properties and CNS penetration).